Electronic Commerce / A Managerial Perspective - Chung Michael H; King David; Lee Jae; Turban Efraim (Prentice Hall International, 2000)
The purpose of this book is to describe what Electronic Commerce is, how it is being conducted and managed, and what the major opportunities, limitations, isssues, and risks are. Foundations of Electronic Commerce, Retailing in Electronic Commerce, Internet Consumers and Market Research, Advertisement in Electronic Commerce, Electronic Commerce for Service Industries, Business-to-Business Electronic Commerce, Intranet and Extranet, EC Strategy and Implementation, Public Policy: From Legal Issues to Privacy, Infrastructure for EC, Economics and Global and Other Issues in EC, Creating Web Pages, Web Programming: Adding Desktop Interactivity and Dynamic Data Access, Software Agents, Glossary, Index.